Superenhanced Removal of Fungal Biofilms by Protease‐Functionalized Amphotericin B Nanocarriers. Issue 2 (6th January 2021) - Weldrick, Paul J.; Hardman, Matthew J.; Paunov, Vesselin N.
Abstract : A strong enhancement in the antifungal activity of amphotericin B (AmpB) encapsulated into shellac nanoparticles (NPs) surface functionalized with protease is reported. These AmpB‐loaded shellac NPs are fabricated by pH‐induced nucleation of aqueous solutions of shellac and AmpB in the presence of Poloxamer 407 (P407) as a steric stabilizer. The AmpB‐loaded shellac NPs are surface coated with the cationic protease Alcalase 2.4L FG. The performance of the AmpB‐encapsulated NPs against Candida albicans is evaluated. The AmpB‐loaded shellac NPs show a remarkable boost of their antifungal action compared to free AmpB when applied to C. albicans in both planktonic and biofilm forms. The surface functionalization with a cationic protease allows the NPs to adhere to the fungal cell walls, delivering AmpB directly to their membranes. Additionally, the hydrolyzing activity of the protease coating degrades the biofilm matrix, thus increasing the effectiveness of the encapsulated AmpB compared to free AmpB at the same concentration. The protease‐coated AmpB‐loaded shellac NPs show no greater toxicity to human adult keratinocyte cells (HaCaT) compared to the free AmpB. These AmpB nanocarriers demonstrat increased efficacy against C. albicans and can be potentially used to treat fungal biofilm infection in the clinic, for example, in recalcitrant chronic wounds. Abstract : Herein, superenhanced removal of fungal biofilms by protease‐functionalized amphotericin B (Amp‐B) nanocarriers is reported. Subsequent functionalization with the cationic protease Alcalase 2.4L FG allows the active nanoparticles to effectively degrade the biofilm and deliver high concentrations of AmpB to the fungal cell membrane, resulting in rapid cell death.